2008
DOI: 10.1029/2008gl033483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atmospheric small‐scale fluctuations on climate sensitivity

Abstract: [1] Climate change scenarios are based on numerical models with finite spatial and temporal resolutions. The impact of unresolved processes is parameterized without taking the variability induced by subscale processes into account. This drawback could lead to an over-/underestimation of the climate sensitivity. The aim of this study is to investigate the impact of small-scale atmospheric fluctuations on the modeled climate sensitivity to increased CO 2 concentration. Using a complex coupled atmosphere-ocean ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Berner et al [40] also found that stochastic backscatter resulted in reductions in systematic errors and improvements in seasonal forecasts. Seiffert and von Storch [41] found that model climate sensitivity to increased carbon dioxide concentrations depends on whether a stochastic backscatter parameterization is employed.…”
Section: [ ]mentioning
confidence: 99%
See 1 more Smart Citation
“…Berner et al [40] also found that stochastic backscatter resulted in reductions in systematic errors and improvements in seasonal forecasts. Seiffert and von Storch [41] found that model climate sensitivity to increased carbon dioxide concentrations depends on whether a stochastic backscatter parameterization is employed.…”
Section: [ ]mentioning
confidence: 99%
“…The generalized Langevin equation which exactly reproduces the QDIA closure equations with subgrid-scale parameterizations is as follows: (41) where:…”
Section: Langevin Equation For Qdia With Subgrid-scale Parameterizationsmentioning
confidence: 99%
“…For the latter purpose, one needs a sufficiently big ensemble of realistic simulations of the past climate, which was not available for the present study. For the stationary response we use the last 100 years of a stabilized 2 3 CO 2 run from Seiffert and von Storch (2008), performed with the same coupled model.…”
Section: A Model and Experimentsmentioning
confidence: 99%
“…Because many of the physical schemes in MIROC3 and MIROC5 differ (Watanabe et al 2010), it is not clear which schemes are largely responsible for determining the structural dependency. The differences in the spatial resolution (and the time step) may also affect the CS of the standard models (Seiffert and von Storch 2008) and the ranges of the CS in the PPEs. Sensitivity experiments in which single or multiple schemes are transferred between the old and new models (with the same spatial resolution and the same time step) would provide insight into the effects of each scheme and the interactions between different schemes (Gettelman et al 2012).…”
Section: Summary and Discussionmentioning
confidence: 99%